How Essential Are Social Goals for Islamic Banks in Indonesia? - Azhar, Neng Zulfa (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2025)
Islamic banking in Indonesia is expected to play a significant role in addressing social welfare, as envisioned by the principles of Maqasid Sharia. However, there remains an ongoing disparity between its financial achievements and societal contributions. While the industry has shown considerable progress in profitability, its broader societal objectives, such as promoting falah—a holistic state of community well-being—remain insufficiently realized. This study examines the extent to which Islamic banking organizations in Indonesia have achieved their societal objectives, focusing on their alignment with the principles of Maqasid Sharia and the pursuit of falah. Despite its financial success, previous research highlights the persistent challenges Islamic banks face in fully realizing their intended societal impact. The adoption of the Islamic Social Banking (ISB) framework is proposed as a viable solution to bridge this gap. This framework provides a targeted strategy for aligning financial operations with social welfare goals. By adopting ISB, Islamic banks can balance profitability with delivering tangible benefits to society, ensuring alignment with Islamic values. This study further underscores the policy implications for regulators of Sharia banking in Indonesia, emphasizing the need for updated legislation and incentives to promote socially responsible practices. These measures can enhance customer trust, support industry initiatives, and foster sustainable development. By adopting the ISB framework, Islamic banks in Indonesia have the potential to redefine their role in the financial sector, shifting from a profit-centric approach to one that emphasizes societal well-being, ensuring that social welfare remains a central focus of the industry’s growth.